2020
DOI: 10.3390/insects11090568
|View full text |Cite
|
Sign up to set email alerts
|

An In-Situ Assessment of Wood-in-Service Using Microwave Technologies, with a Focus on Assessing Hardwood Power Poles

Abstract: Wooden power poles and their ongoing inspection represent a significant investment for most electrical power utilities. This study explored the potential for using microwave fields to non-invasively assess the state of hardwood power poles in a field experiment. Two strategies were assessed: 2.4 GHz microwave field transmission through the pole; and mutual coupling between antennae using a 10.525 GHz radar module applied to the surface of the pole. Both systems distinguished between sound hardwood poles and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is unclear whether they can attack denser timbers, but the results indicate that the device has a limited ability to detect infestations in denser timbers. While this would be a limitation in larger timbers and poles (Brodie et al, 2021), it poses less of an issue in building components. Subsequent trials using 38 mm thick radiata pine samples with densities ranging from 392 to 781 kg/m 3 showed that the device could only detect termites in samples with densities less than or equal to 512 kg/m 3 (Table 4).…”
Section: Effect Of Wood Density and Grain Orientationmentioning
confidence: 99%
“…It is unclear whether they can attack denser timbers, but the results indicate that the device has a limited ability to detect infestations in denser timbers. While this would be a limitation in larger timbers and poles (Brodie et al, 2021), it poses less of an issue in building components. Subsequent trials using 38 mm thick radiata pine samples with densities ranging from 392 to 781 kg/m 3 showed that the device could only detect termites in samples with densities less than or equal to 512 kg/m 3 (Table 4).…”
Section: Effect Of Wood Density and Grain Orientationmentioning
confidence: 99%
“…The HB 100 Doppler radar sensor is widely used for motion detection thanks to its low cost and high reliability [11][12]. Recently, the HB 100 sensor was used for additional functions such as underground metal detection [13] or wooden pole inspection in forests [14]. Unfortunately, up to now, there are very few studies on the use of the sensor for detecting additive materials in concrete.…”
Section: Introductionmentioning
confidence: 99%